Benchmarking Industri Halal: Indonesia dan Malaysia - Maolana, Tommy; Hidayat, Rahmat (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This study aims to conduct a comparative benchmarking analysis of the halal industry operational frameworks in Indonesia and Malaysia. The primary focus is to identify best practices, regulatory gaps, and strategic opportunities for collaboration to strengthen the halal ecosystem in the ASEAN region. Employing a descriptive qualitative approach through a systematic literature review, this research collects and synthesizes data from academic articles, official policy documents, and industry reports. The analysis utilizes a comparative benchmarking framework to evaluate key dimensions such as institutional governance, certification mechanisms, infrastructure development, and market strategies in both countries. The findings reveal that while Indonesia possesses a vast domestic market and natural resource advantages, it faces challenges in bureaucratic complexity and low halal literacy among small and medium enterprises. In contrast, Malaysia demonstrates institutional excellence through JAKIM’s centralized certification system and an integrated halal supply chain, yet struggles with product diversification and international standard harmonization. The study concludes that benchmarking Malaysia’s institutional strengths can offer valuable insights for Indonesia to enhance its regulatory framework and competitiveness. Furthermore, strategic collaboration between the two nations holds significant potential to establish a synergistic ASEAN Halal Hub. This research contributes to evidence-based policy formulation and provides a foundation for future empirical studies.